2014
DOI: 10.1039/c4ra08771b
|View full text |Cite
|
Sign up to set email alerts
|

A turn-on NIR fluorescent probe for the detection of homocysteine over cysteine

Abstract: A BODIPY-based turn-on NIR fluorescent probe containing a partially exposed aldehyde group at the meso position for the detection of homocysteine over cysteine was developed. Such a probe is potentially useful for the discrimination of Hcy from Cys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Our group introduced the formyl group to the meso position of ac onformationally restricted BODIPY skeleton to establish turn-onf luorescent probe 34 for Cys/Hcy. [72] The time-dependent measurements demonstrated that the probe reacted faster with Hcy than Cys and the kinetic modes provided ap otential application to discriminateH cy from Cys. Hao, Jiao, and co-workersr eported 2-formyl BODIPY derivative 35.…”
Section: Probesf or Sulfhydryl Amino Acidmentioning
confidence: 95%
“…Our group introduced the formyl group to the meso position of ac onformationally restricted BODIPY skeleton to establish turn-onf luorescent probe 34 for Cys/Hcy. [72] The time-dependent measurements demonstrated that the probe reacted faster with Hcy than Cys and the kinetic modes provided ap otential application to discriminateH cy from Cys. Hao, Jiao, and co-workersr eported 2-formyl BODIPY derivative 35.…”
Section: Probesf or Sulfhydryl Amino Acidmentioning
confidence: 95%
“…However, fluorescence quenching probes suffer from low signal-to-noise ratio, so that fluorescence probes using "turn-on" mode are preferred. But only a few aldehyde-functionalized "turn-on" probes have been reported for selective detection of Hcy, such as pyrene-based dyes [20], and BODIPY [21]. For example, Wang and coworkers studied a dansyl azide analogue fluorescent probe for the selective detection of Hcy [22].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to these classical techniques, in the past two decades, a number of chromo-fluorogenic probes for biothiol detection have been reported [22][23][24]. Most of the described examples are based on the chemodosimeter approach and are synthesized taking into account the nucleophilic character of thiol moieties in these biomolecules [25][26][27][28][29][30][31]. Also, the displacement approach has been extensively used to design biothiol selective chromo-fluorogenic probes.…”
Section: Introductionmentioning
confidence: 99%